Trends in Worldwide Research in Inflammatory Bowel Disease Over the Period 2012–2021: A Bibliometric Study - Li, Kemin; Feng, Chenzhe; Chen, Haolin; Feng, Yeqian; Li, Jingnan (Frontiers in Medicine, 2022)
Background Inflammatory bowel disease (IBD) is a continuously increasing and worldwide disease, and the number of publications of IBD has been expanding in the past 10 years. The purpose of this study is to analyze the published articles of IBD in the past decade via machine learning and text analysis and get a more comprehensive understanding of the research trends and changes in IBD in the past 10 years. Method In November 2021, we downloaded the published articles related to IBD in PubMed for the past 10 years (2012-2021). We utilized Python to extract the title, publication date, MeSH terms, and abstract from the metadata of each publication for bibliometric assessment. Latent Dirichlet allocation (LDA) was used to the abstracts to identify publications' research topics with greater specificity. Result We finally identified and analyzed 34458 publications in total. We found that publications in the last 10 years were mainly focused on treatment and mechanism. Among them, publications on biological agents and Gastrointestinal Microbiome have a significant advantage in terms of volume and rate of publications. In addition, publications related to IBD and coronavirus disease 2019(COVID-19) have increased sharply since the outbreak of the worldwide pandemic caused by novel β-coronavirus in 2019. However, researchers seem to pay less attention to the nutritional and psychological status of patients with IBD. Conclusion IBD is still a worldwide disease of concern with the publication of IBD-related research has expanded continuously over the past decade. More research related nutritional and psychological status of patients with IBD is needed in the future. Besides, it is worth noting that the management of chronic diseases such as IBD required additional attention during an infectious disease epidemic.